Value-saturated Education in Erzsébet Camps in Zánka, Hungary - Jancsák Csaba (Belvedere Meridionale Szeged, 2020)
The Erzsébet Camp in Zánka is located in the Balaton Highland, between Tihany and Badacsony. The Erzsébet Camps are one of the largest youth-project program in Hungary. Research data collection started in 2017, and it was carried out in three periods. The present study conducted analyses on a database compiled from findings of questionnaires administered to campers (2017, 2018 and 2019) and their chaperones (2018 and 2019). Data collection from the children and chaperones took place at the end of each camp shift and comprised of self-administered anonymous questionnaires with ten question blocks. The study conducts analyses of the database compiled from the main answers of more than 18,000 participants. Our research, exploratory in its nature, set out to compile the ”value map” of the Erzsébet Camps. The main focus of our interest was the added value and developmental effects of the camps with respect to campers. The another research question was what social values are transmitted and the preservation of which social values is supported by the Erzsébet Camps.
Keywords: Társadalomtudományok; Oktatástudomány